ANALISIS PREDIKSI KEBANGKRUTAN USAHA PADA KSP. MADANI NTB - I Nengah Arsana; Baehaki Syakbani (Valid: Jurnal Ilmiah, 2017)
This study aims to determine the overall picture of the financial performance of KSP. Madani NTB during 2007 to 2016 based on the Altman Z-Score method that has been equipped with a cut-off point to determine the classification of bankruptcy. Altman uses five financial ratios destined for the company : Working Capital to Total Assets (X1), Retained Earning to Total Assets (X2), Earning Before Interest and Tax to Total Assets (X3), Book Value Equity of Total Liabilities (X4) And Sales to Total Assets (X5). This study is a descriptive study conducted on KSP.Madani NTB during 2007 to 2016. The results of this study indicate that the highest Z-Score score of 21.94 in 2007, the lowest Z-Score score of 8.56 in 2012 or The average Z-Score score of 14.02 is above the cut-off point of Z > 2.90 entering the criteria of not going bankrupt (the company is in good health)